If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7c+62=2c+67
We move all terms to the left:
7c+62-(2c+67)=0
We get rid of parentheses
7c-2c-67+62=0
We add all the numbers together, and all the variables
5c-5=0
We move all terms containing c to the left, all other terms to the right
5c=5
c=5/5
c=1
| x-10/2=-13 | | 24-8x=-2+6(x+2) | | 8b+5(b-3)=245 | | 69=12x+15 | | -4.5=9y | | 5(3+x)-8=22 | | 22=6b-18 | | 9y-32=67 | | f/6+33=40 | | 72=4x-4 | | 9=x+4+5 | | 94=2(u+17) | | 2(x-3)^2+8=0 | | 2x-6+2x-6=2x-7 | | 10x-79=2x+59 | | 70/80=x/8 | | 2(x-3)2+8=0 | | 4/5x=45 | | 7080=x8 | | -10y=-1000 | | j/3+14=18 | | 2/7x=77 | | -8=1+5x-4 | | 11(x+10)-23=12x+220 | | 7/8x=96 | | 7x-2x-12=-2 | | 6+4(7x–2)=6+28x–8 | | 7/8x=78 | | z/7+9=-18 | | Y=x2-2x+5 | | 144-4x=112 | | 2s+1=1 |